Canyon Cinema : The Life and Times of an Independent Film Distributor - MacDonald, Scott, 1942- (Book collections on Project MUSE., 2007)
Bringing alive a remarkable moment in American cultural history, Scott MacDonald tells the colorful story of how a small, backyard organization in the San Francisco Bay Area emerged in the 1960s and evolved to become a major force in the development of independent cinema. Drawing from extensive conversations with men and women crucial to Canyon Cinema, from its newsletter Canyon Cinemanews, and from other key sources, MacDonald offers a lively chronicle of the life and times of this influential, idiosyncratic film exhibition and distribution collective. His book features many primary documents.